Environmentally friendly disposal of used automotive oil filters: legislative aspects and technology - Hanoshenko, Olena; Stepova, Olena; Chukhlib, Yullia; Kostiantyn, Leshchuk; Yanovych, Yurii; Bilotserkivsk, Natalia (Ecological Questions, 2021)
Due to external environmental concerns, new European Union (EU) legislation is currently increasing the requirements for the disposal of vehicles and their used components. Used automotive oil filters (UAOF) are both a threat to the environment and contain valuable components for reuse. Waste minimization, their environmentally safe disposal, neutralization, utilization and conservation of natural resources is an urgent global problem. It is the legislative rationale for solving this problem and the search for an environmentally friendly UAOF recycling technology that is the purpose of this study. The legislative aspects were studied by reviewing the current regulatory and legislative documents of Ukraine and the EU countries, as well as scientific literature. The reviewed scientific literature was collected from three main databases: Scopus, Web of Science, ResearchGate, where the corresponding keywords. It was found that the current legislation in the field of waste management is not perfect and has many gaps and contradiction. The search for environmentally friendly technology was carried out in different temperature conditions and using different amounts of detergents, which made it possible to determine the most effective detergent sodium percarbonate (Na2CO3∙1.5 H2O2) - a chemical compound that is a safe and convenient carrier of hydrogen peroxide. As a result of the conducted theoretical and experimental researches the complex utilization technology of UAOF and the detailed algorithm is presented. The scheme process plant for washing the contaminated filter paper and the washing technology, which allows retrieving resource valuable components, has been developed. It is experimentally proved that pre-treatment of the filter paper with a washing solution allows reducing the number of pollutants, namely the content of waste oil is reduced by 55%, and the number of pollutants in the flue gases by 89% of sulphur (IV) oxide, 15% of nitrogen (IV) oxide, 66% of carbon (ІІ) oxide, 86% of carbon (soot).